Pengaruh Model Pembelajaran Inkuri Terbimbing terhadap Keterampilan Proses Sains Peserta Didik Kelas VIII SMPN 40 Makassar - Andi Sriwaru Usman; Sitti Rahma Yunus; Hasanuddin Hasanuddin (Universitas Negeri Makassar, 2023)
This study aims to find out 1) improvement of science process skills of the students of eight grade SMPN 40 Makassar taught using guided inquiry model in the subject matter of work and simple plane, 2) improvement of science process skills of the students of eight grade SMPN 40 Makassar taught using conventional learning model in the subject matter of work and simple plane, and 3) the effect of the guided inquiry model in improving science process skills of eight grade SMPN 40 Makassar taught using conventional learning model in the subject matter of work and simple plane. This research is quasi-experimental research (quasi-experiment) with Nonequivalent Control Group Design research design. The population of this research is all students of eight grade SMPN 40 Makassar. Sampling uses Purposive Sampling technique so that it is obtained class VII.2 as the experimental class and class VIII 2 as the control class. Data processing result of this study using descriptive analysis, the mean N-gain score of science process skills of students in the experimental class is 0,71 in the high category and the control class is 0,61 in the medium category. Based on results of infertial statistical analysis using hypothesis testing, it was found that Ho was rejected and H1 was rejected so that it could be concluded that there was an influence of guided inquiry learning model on science process skills of eight grade SMPN 40 Makassar study in the subject matter of work and simple plane.